Evidence for neuronal degeneration and dendritic plasticity in cortical pyramidal neurons of Huntington's disease: a quantitative Golgi study - Sotrel, A; Williams, R S; Kaufmann, W E; Myers, R H (Neurology, 1993)
Aided by a computer microscope, the Eutectic Neuron Tracing System, we performed a quantitative analysis of 59 rapid Golgi-impregnated pyramidal neurons from the third and fifth prefrontal cortical layers (P III and P V neurons) in tissue sections obtained from seven autopsied Huntington's disease (HD) patients (grades 2 through 4) and 59 corresponding cells from eight age-matched control cases. Relative to controls, P III HD neurons had a significant increase in the number of primary dendritic segments arising from soma, total dendritic length, and total surface area. The HD cells also had significantly more dendritic branches at three intervals of measurement in a Sholl diagram (100 microns, 200 microns, and 400 microns from the soma) and a significant increase in the number of dendritic branching points. The dendritic spine density in P III HD neurons was comparable to that of control subjects and significantly lower than that in P V HD cells. The total number and the total density of dendritic swellings were significantly increased in both P III and P V neurons, being most numerous in grades 2 and 3 cases. Rare withered cells with shrunken dendritic trees, harboring few spines and numerous varicosities on their dendritic shafts, were present in HD but not in control cases. Thus, while a small fraction of prefrontal cortical pyramidals degenerates in HD, the plasticity of the remaining pyramidal neurons, evidenced as an orderly augmentation of the dendritic tree, may represent a compensatory response sufficient to maintain relatively normal metabolic function of the cortex in most adult-onset cases.